ASSESSMENT OF MORPHOMETRIC INDICATORS OF THE THYMUS OF WHITE RATS WITH MG DEFICIENCY - Turdiyev M.R. (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Annatation: white seed tissue of rats without histological structure of the thymus Research, cell culture composition and the analysis of the indicators was immunogistokimyoviy qiyo. Results the analysis that magnesium alimentar yetishmovchiligida parenxima this member-strong balance the violation of limfoid tissue morfometrik indicators, limfoid and will determine the level of reduction in the number of cells express immunogistokimyoviy markyorlar. These changes decrease the body's immune response suppression and protection with appeared.